Magnetohydrodynamic seismology of a coronal loop system by the first two modes of standing kink waves - Guo Y.; Erdélyi R.; Srivastava A.K.; Hao Q.; Cheng X.; Chen P.F.; Ding M.D.; Dwivedi B.N. (My University, 2025)
We report the observation of the first two harmonics of the horizontally polarized kink waves excited in a coronal loop system lying southeast of AR 11719 on 2013 April 11. The detected periods of the fundamental mode (P1), its first overtone (P2) in the northern half, and that in the southern one are 530.2 ± 13.3, 300.4 ± 27.7, and 334.7 ± 22.1 s, respectively. The periods of the first overtone in the two halves are the same considering uncertainties in the measurement. We estimate the average electron density, temperature, and length of the loop system as (5.1 ± 0.8) × 108 cm-3, 0.65 ± 0.06 MK, and 203.8 ± 13.8 Mm, respectively. As a zeroth-order estimation, the magnetic field strength, B = 8.2 ± 1.0G, derived by the coronal seismology using the fundamental kink mode matches with that derived by a potential field model. The extrapolation model also shows the asymmetric and nonuniform distribution of the magnetic field along the coronal loop. Using the amplitude profile distributions of both the fundamental mode and its first overtone, we observe that the antinode positions of both the fundamental mode and its first overtone shift toward the weak field region along the coronal loop. The results indicate that the density stratification and the temperature difference effects are larger than the magnetic field variation effect on the period ratio. On the other hand, the magnetic field variation has a greater effect on the eigenfunction of the first overtone than the density stratification does for this case. © 2015. The American Astronomical Society. All rights reserved.